Development of Website-Based Learning Media for Listening Skills for Puppet Story Materials at the Junior High School Level - Khusna, Dina Novita; Insani, Nur Hanifah (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to design, develop, and evaluate website-based Javanese language learning media that are designed innovatively, interactively, and easily accessible to students and teachers. Another objective is to ensure that this learning media is in accordance with user needs and supports an effective learning process. The type of research used is research and development (R&D) based on the theory put forward by Sugiono, which includes systematic steps in designing and testing learning products. Data collection was carried out through questionnaires distributed to students and teachers to identify their needs, where the results were analyzed using qualitative and quantitative descriptive approaches. Product validation was carried out by several parties, including students as the primary users, media validators to assess the quality of design and interactivity, and material validators to assess the accuracy of learning content. Based on the validation results, media experts and material experts assessed this product as